Judicialization in international security: A theoretical concept and some preliminary evidence - Aletta Mondré; Bernhard Zangl (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
Many claim a process of judicialization of international dispute settlement procedures is taking place. In order to capture this ongoing process we introduce an analytical framework to assess the degree of judicialization of international dispute settlement procedures. We then proceed to present preliminary results of applying this framework to the procedure and practice of dispute settlement in the United Nations Security Council. In our concept, judicialization means that international dispute settlement procedures increasingly incorporate the normative principle of impartiality, i.e. the principle of a comparable treatment of comparable breaches of law. We use a graded scale ranging from purely diplomatic to predominantly judicial procedures to assess the degree of judicialization of any given dispute settlement procedure. From our institutionalist point of view, it is entirely an empirical question whether - and if so when - judicialized dispute settlement procedures lead to a corresponding practice of judicialized dispute settlement. For this reason we analyze in a second step the corresponding practice of dispute settlement. The degree of judicialization of the dispute settlement procedure within the framework of the United Nations Security Council remains low. Nonetheless, our comparison of the periods 1974-1983 and 1990-1999 suggests so far an increasing judicialization of the dispute settlement practice within the Security Council. – – Viele Beobachter stellen eine Judizialisierung von internationalen Streitbeilegungsverfahren fest. Um diesen fortlaufenden Prozess erfassen zu können, stellen wir ein Analyseraster für die Bestimmung des Ausmaßes von Vergerichtlichung internationaler Streitbeilegungsverfahren vor. Danach präsentieren wir vorläufige empirische Ergebnisse der Anwendung unseres Rasters auf das Verfahren und die Praxis der Streitbeilegung im Sicherheitsrat der Vereinten Nationen. Unserem Konzept zu Folge bedeutet Judizialisierung (Vergerichtlichung) von internationalen Streitbeilegungsverfahren die zunehmende Einbeziehung des normativen Grundsatzes von Unparteilichkeit, also einer Gleichbehandlung von gleichartigen Rechtsverletzungen. Wir verwenden eine abgestufte Skala, die von rein diplomatischen bis zu vornehmlich gerichtsförmigen Verfahren reicht, zur Bestimmung des Grades von Vergerichtlichung beliebiger Streitbeilegungsverfahren. Aus unserer institutionalistischen Perspektive ist es eine empirische Frage, ob - und wenn ja, wann - juridizialisierte Streitbeilegungsverfahren zu einer entsprechenden Praxis der Streitbeilegung führen. Aus diesem Grund untersuchen wir in einem zweiten Schritt die Praxis der Streitbeilegung. Das Ausmaß von Vergerichtlichung des Verfahrens im Sicherheitsrat der Vereinten Nationen ist weiterhin gering. Nichtsdestotrotz weist bislang der Vergleich der Zeiträume 1974-1983 und 1990-1999 auf eine zunehmende Judizialisierung der Streitbeilegungspraxis im Sicherheitsrat hin.
Keywords: 340; Recht; Internationale Sicherheit; Theorie; Internationales Recht; Sicherheitspolitik